2015
DOI: 10.1111/ctr.12568
|View full text |Cite
|
Sign up to set email alerts
|

The use and value of procalcitonin in solid organ transplantation

Abstract: Procalcitonin (PCT) has been increasingly used as a biomarker of bacterial infection and as a tool to guide antimicrobial therapy, especially in lower respiratory tract and bloodstream infections. Despite its increased use, data in patients with solid organ transplants are limited. Even without the presence of infection, PCT increases as a result of surgical procedures during transplantation, implantation of devices, and use of induction immunosuppressive therapy. The risk of infection is also higher in solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…86 Several studies have evaluated the utility of procalcitonin measurement for detecting and differentiating bacterial infection from other solid organ transplant complications, 87-94 reviewed in. 95 Importantly, procalcitonin levels are impacted by surgery as well as by ATG administration which may decrease the utility of this assay in first week post-transplant. 95 (Figure 1).…”
Section: Iag Nos Ti C Te S Tingmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Several studies have evaluated the utility of procalcitonin measurement for detecting and differentiating bacterial infection from other solid organ transplant complications, 87-94 reviewed in. 95 Importantly, procalcitonin levels are impacted by surgery as well as by ATG administration which may decrease the utility of this assay in first week post-transplant. 95 (Figure 1).…”
Section: Iag Nos Ti C Te S Tingmentioning
confidence: 99%
“…95 Importantly, procalcitonin levels are impacted by surgery as well as by ATG administration which may decrease the utility of this assay in first week post-transplant. 95 (Figure 1).…”
Section: Iag Nos Ti C Te S Tingmentioning
confidence: 99%
“…In a post‐transplant setting, studies have shown the benefit of PCT for diagnosis of bacterial infection and differentiation from acute cellular rejection . However, the influences of the length of surgery and immunosuppression therapy have not been sufficiently examined . In this study, we focused on the relationship between post‐transplant sepsis and pretransplant PCT that was unaffected by surgical factors or post‐transplant management.…”
Section: Discussionmentioning
confidence: 99%
“…Serum procalcitonin (PCT) is used as a biomarker of bacterial infection and sepsis in a number of areas, and may be useful for early detection of infection and differentiation from non‐infectious complications after LT . However, it is difficult to exclude the effects of highly invasive surgical procedures and post‐transplant immunosuppression therapy on the serum PCT level …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be used to guide determination of the length of the antimicrobial therapy and to assess the response to treatment. 13 Serial measurement of serum procalcitonin levels can help detect early bacterial infections. In a retrospective study invo lving kidney transplant recipients, patients with serum CRP levels 118 > 10 mg/dL or procalcitonin levels > 8.8 ng/mL have been reported to have worse prognosis.…”
Section: Discussionmentioning
confidence: 99%